Secrecy Rate Maximization for Active RIS-Aided Robust Uplink NOMA Communications - Singh, Sandeep; Raviteja, Allu; Singh, Keshav; Singh, Sandeep Kumar; Kaushik, Aryan; Ku, Meng-Lin (IEEE wireless communications letters, 2024)
In this letter, we investigate the performance of an active reconfigurable intelligent surface (RIS)-aided uplink non-orthogonal multiple access (NOMA) network in the presence of an eavesdropper (Eve). We formulate a sum secrecy rate maximization while ensuring a minimum performance at each user within available resource constraints considering the norm-bounded imperfect channel state information (CSI) at the Alice and Eve. To tackle the non-convex nature of the formulated problem, we propose an alternating optimization (AO) based algorithm that jointly optimizes the combining vector, power allocation at each user, and beamforming at the RIS. The efficacy and convergence of the proposed algorithm are validated via extensive numerical simulation. The potential of active RIS in integration with NOMA, compared to passive RIS, space division multiple access (SDMA), and orthogonal multiple access (OMA), towards a robust and secure uplink is demonstrated. Finally, we discuss the impact of key system parameters such as maximum power budget at each user and RIS, and CSI error on the secrecy performance.